2005
DOI: 10.1177/153537020523000109
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokines and the Hypermetabolism of Children with Sickle Cell Disease

Abstract: Sickle cell anemia (HbSS) includes chronic inflammation, but the origin is unclear. We hypothesized that in stable HbSS patients the inflammation was associated with hypermetabolism. We compared selected hypermetabolic and key immunomodulator indicators in HbSS versus control children and examined associations between measures of hypermetabolism and inflammation. Twelve fasting asymptomatic HbSS children 6-12 years and 9 controls matched for age, gender and fat mass (FM) were studied. Proportional reticulocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 32 publications
5
92
2
Order By: Relevance
“…Recent understanding of HbSS pathology includes baseline inflammation, which so far is defined mainly by marked leukocytosis linked with disease severity (33). We have shown that in patients with HbSS, C-reactive protein, a sensitive indicator of inflammation, is an important predictor of REE adjusted for FFM (21). It is therefore possible that consideration of inflammatory factors could further increase the precision of predictive equations for REE in HbSS subjects (14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent understanding of HbSS pathology includes baseline inflammation, which so far is defined mainly by marked leukocytosis linked with disease severity (33). We have shown that in patients with HbSS, C-reactive protein, a sensitive indicator of inflammation, is an important predictor of REE adjusted for FFM (21). It is therefore possible that consideration of inflammatory factors could further increase the precision of predictive equations for REE in HbSS subjects (14).…”
Section: Discussionmentioning
confidence: 99%
“…Average dietary protein (HbAA, 1.57 ± 0.26 g/kg body weight per day; HbSS, 1.79 ± 0.38 g/kg body weight per day) and energy (HbAA, 51 ± 13 kcal/kg body weight per day; HbSS, 60 ± 16 kcal/kg body weight per day) intakes were not different between the groups. Physical characteristics and hematology for the participants are shown in Table 1 and are described in detail elsewhere (21). There was no significant age difference between the HbSS and HbAA groups.…”
Section: Subjects' Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemokines and their receptors have been implicated in the development of vascular inflammatory disorders, and, in this regard, higher levels of proinflammatory cytokines and chemokines have been reported to be present in patients with sickle cell disease (4)(5)(6).…”
mentioning
confidence: 99%